Seasonal Affective Disorder on the Stock Market: Nordic Evidence - Malinen, Rasmus (My University, 2016)
Seasonal Affective Disorder (SAD) causes seasonal depression in a part of the population in several countries. It presents itself, when daylight hours decrease and has been found to be more prevalent, when moving away from the equator. This thesis examines the implications and inefficiencies the disorder may cause on some of the northernmost stock markets, the stock markets of the Nordic countries. The topic is approached from the perspectives of efficient markets and behavioral finance. The efficient market part presents the principles of asset pricing on efficient markets. In the behavioral finance part, the irrational behavior of investors is explained through psychological biases. The chapter also introduces the concept of limits to arbitrage and four anomalies that are connected to the SAD phenomenon. In the empirical part, a regression is run for large cap and small cap indices from Finland, Sweden, Denmark and Norway. Large cap and small cap indices are examined separately to find out, if SAD affects large and small companies differently. Iceland is studied as comparison to these countries, because the prevalence of SAD is especially low there regardless of its extremely northern location. Daily returns of these indices are regressed on a SAD variable, which measures the length of night at a certain latitude, and a fall dummy, which allows the effect of SAD to be asymmetrical. A tax-loss dummy and a Monday dummy are used as additional explanatory variables. A statistically significant SAD effect is found in all other indices, but the Danish small cap index and the Icelandic All Share index. The effect is asymmetrical for all indices excluding the Finnish large cap index. This means that the effect shifts returns from fall to winter. The coefficients for SAD are quite consistent for the large cap indices, varying from 0,025 % in Norway to 0,022 % in Finland, Sweden and Denmark. The consistency of the coefficients is lower for small cap indices, ranging from 0,028 % in Sweden to 0,014 % in Finland. Based on these results, no claim can be made about small cap companies experiencing a larger SAD effect or vice versa.
Keywords: Seasonal Affective Disorder; Stock Returns; Efficient Markets; Behavioral Finance; Stock Market Anomalies; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|